(untitled) (Fiep Bulletin - online, 2020)
Fibromyalgia is a chronic noninflammatory pain syndrome, with manifestations in the musculoskeletal system, and may present symptoms in other devices and systems, where the main characteristic is pain, requiring mechanisms that favor the patient’s quality of life, such as physical activities. Thus cycling is a possibility of low impact activity. This research aims to analyze the contributions of cycling in a person with fibromyalgia, highlighting the benefits of sport in maintaining and preserving well-being and quality of life. This research addresses the case study, in a context of cross-sectional study, in the qualitative research paradigm, in a male, diagnosed with fibromyalgia, with 41 years and 04 months, a civil servant, during the year 2019. Due to his injuries and pain, he had not played sports regularly for a year. During the period of diagnosis of fibromyalgia, this individual started to search for activities that reduced tiredness and, especially, pain. With the oriented practices, it is first noticed that the bikefit was fundamental in the regulation of the bicycle for the practical sessions, since the activities took place in indoor and outdoor situations. Over the three months of the sessions, they were divided into 13 weeks with four weekly sessions totaling 52 interventions lasting an average of two hours (120 minutes), respecting the routine of the sessions and the perception of the involved according to the Effort Perception Rate. (TPE). It can be concluded that the interval training sessions had a positive effect, as improvements in speed, strength and endurance were observed; as the sessions had short intervals, but with intense effort did not cause injuries and pain at the end of the interventions.